THE EFFECTIVENESS OF MULTIPLE INTELLIGENCE-BASED QUANTUM LEARNING MODEL ON SOCIAL SKILLS AND SOCIAL STUDIES LEARNING OUTCOMES (A QUASI-EXPERIMENTAL STUDY AT SMP NEGERI 23, 32, AND 41 BANDUNG CITY) - Hari Rudiana; Jajang Hendar Hendrawan; Neneng Tripuspita (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This research is motivated by findings that the achievement of IPS learning outcomes and student social skills at SMP Negeri 23, 32, and 41 Bandung City still tend to be in the medium to low category. The purpose of this study is to determine the effectiveness of the Multiple Intelligence-based Quantum Learning model in increasing social skills and IPS learning outcomes. This study uses a quantitative method with a Quasi-Experimental approach and Non-equivalent Control Group Design. The research subjects were grade VIII students totaling 192 individuals, involving experimental and control groups at SMP Negeri 23, 32, and 41 Bandung City. Data collection was carried out through pre-tests, post-tests, and questionnaires using a Likert scale. Hypothesis testing showed that the mean IPS learning outcome for the control class was 78.54 and for the experimental class was 78.54. The Independent Sample t-test showed a significance value of 1.000, which is greater than 0.05, indicating no significant difference in IPS learning outcomes between the two groups. Consequently, the Multiple Intelligence-based Quantum Learning model has not shown significant effectiveness in improving IPS learning outcomes compared to conventional learning. However, practically, this model provides a large influence on the quality of the learning process through more active student involvement, increased social interaction, and the development of intelligence potentials. It is concluded that while statistical effectiveness was not found for learning outcomes, the model creates a more active, interactive, and pleasant learning atmosphere and encourages student involvement in the development of social skills.